Pendampingan Pembelajaran Matematika Berbasis Permainan Tradisional di Oemah Matematika, Metro, Lampung - Pika Merliza; Juitaning Mustika; Yunita Wildaniati; Selvi Loviana; Yuyun Yunarti; Endah Wulantina (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
The purpose of community service is to mentor children in the Oemah Mathematika environment, Yosorejo sub-district, East Metro, Indonesia in understanding mathematics learning materials by utilizing traditional games including snakes and ladders, dakon (congklak) and tablecloth games. Through this series of traditional games, children learn the basic material for integers, lowest common multiple (LCM) and highest common factor (HCF), as well as material for flat shapes. The results of community service showed that the mentoring process for children at Oemah Mathematika went smoothly, the children felt enthusiastic about learning basic mathematics materials through traditional games. The mentoring process makes learning mathematics fun for them and fosters a love for the culture particularly tradisional games which has begun to be eliminated by the existence of IT-based games.